PENGEMBANGAN SOAL HOTS BERBASIS PERMAINAN ULAR TANGGA PADA MATA KULIAH TELAAH EKONOMI SMA - Heri Supranoto (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
The purpose of this study is to Develop the HOTS Problem Based Snake Stage Game which can be used as a fun evaluation tool and can improve students' high-level This research uses 4D development model (Define, Design, Develop and Dissemination). However, this research is only at the develop stage. In the Dissemination stage is not done due to time and cost constraints. The first stage of this research is to analyze the problems and needs of students. Next the second phase is designing the product. At this stage begin to compose the grid problem and the problem of HOTS and make the media snake ladder. The resulting product is then validated by a material expert and linguist. After repaired and declared valid, then tested into small groups of 10 students who were obtained at random. Tests conducted by spreading the questionnaire to find out how the response of students. Questionnaire is then analyzed to find out how the value of percentage obtained and the level of feasibility of products that have been developed. Based on the results of research that has been done obtained the data as follows: The validation results for material experts said that the matter of HOTS included in the category is very reasonable and the linguist also said the problem included in the category is very feasible. While in small group trial the value of presentase reached 84.6% included in the category is very feasible. Based on this it can be concluded that the medium of SOAL HOTS is very feasible to be used as an evaluation supplement for students of 4th semester of High School Economics Course.